CORRELATION OF MOUTH BREATHING HABITS TO DENTAL MALOCCLUSIONS: KORELASI KEBIASAAN BERNAPAS MELALUI MULUT TERHADAP JENIS MALOKLUSI GIGI - Ketut Virtika Ayu; I Dewa Gede Budijanana; Norman Hidajah; Surwandi Walianto (Interdental Jurnal Kedokteran Gigi (IJKG), 2023)
Introduction: one of the malocclusion’s etiology is bad habits such as mouth breathing habit. The purpose of this study was to determine the relationship between the mouth breathing habit through with the type of malocclusion. Materials and Method: the sampling method used was purposive sampling obtained from giving questionnaires to parents and clinical examination of the oral cavity of students at SDN 17 Dauh Puri Denpasar. The number of samples with mouth breathing habit were 50 samples. Classification of dentition malocclusion in students was assessed using a modified Dewey Angle Classification. Data analysis used the chi-square test. Results and Discussion: the results of this study were that the mouth breathing habit was more dominant in the Class I Angle type 2 Dewey malocclusion with a total of 25 students (50%) and in the Class I Angle type 4 Dewey malocclusion with a total of 14 students (28%). Conclusion: the conclusion of this study is that there is a significant relationship between the mouth breathing habit and the type of malocclusion.